Pramipexole in peritoneal dialysis patients with restless legs syndrome (RLS): a protocol for a multicentre double-blind randomised controlled trial. Issue 2 (18th February 2020) - Ma, Tian-tian; Yang, Zhikai; Zhu, Sainan; Zhao, Jing-hong; Li, Yi; Sun, Fu-yun; Zhao, Nan; Xiong, Zu-ying; Xiong, Zi-bo; Dong, Jie
Abstract : Introduction: Restless legs syndrome (RLS) is a common neurological sensorimotor disorder among patients with end stage renal disease. This clinical trial aimed to provide evidence on the efficacy and safety of pramipexole in patients with uremic RLS receiving peritoneal dialysis (PD). Methods and analysis: This is a 12-week, multicentre, randomised, double-blind, placebo-controlled clinical trial. In total, 104 patients with uremic RLS receiving PD will be enrolled from four hospitals and randomly assigned in a 1:1 ratio to either placebo or pramipexole. We will determine the efficacy of pramipexole in the improvement of International RLS Study Group Rating Scale as the primary outcome, while responder rates for other RLS scales at week 12, change from baseline to week 12 for psychological status, sleep disorder and quality of life and blood pressure represent the secondary outcomes. Ethics and dissemination: The study was approved by the ethics committees of Peking University First Hospital, Xinqiao hospital of Army Medical University, Cangzhou Center Hospital and Peking University Shenzhen Hospital. The results will be disseminated in peer-reviewed journals. Trial registration number: NCT03817554